Influência do hidrogênio na tenacidade à fratura quase estática de juntas dissimilares amanteigadas e soldadas com ligas de níquel - Silva, Roneles de Santana (2018)
A sequence of failures in dissimilar welded joints in components of offshore structures subjected to cathodic protection has been verified in recent years. The flaws occurred at the interface of the buttery flange of ARBL steels with the Inconel 625 nickel alloy. This fact has generated a lot of research, which looks for the probable causes and solutions for the phenomenon. The present work aims to analyze the susceptibility of dissimilar welded union to hydrogen embrittlement from the cathodic protection system through quasi-static fracture toughness tests (CTOD), as well as the mechanical and microstructural behavior of the dissimilar buttery interface of the steel AISI 4130. The MIG welding process was used in the buttery welding and closure of the dissimilar joint. The influence variables analyzed were the conventional and pulsed current modes, the types of addition metals, the thermal stress relief treatment (TTAT) and the hydrogen from the cathodic protection system. The response variables were: the microstructure and the microhardness at the interface of the buttery solder, the dissimilar joint hardness and the toughness to the quasi-static fracture of the ZTA (Thermally Affected Zone) of the buttery and welded joint. The results showed that the welding procedure is fundamental for the control of the Partially Diluted Zones (ZPDs) in the buttery welding interface. Regardless of the mode of current and the addition metal it was found that TTAT made the interface more fragile. The results also showed that the type of addition metal significantly influenced the fracture toughness response of the dissimilar joint; the values of CTOD showed that the fracture toughness of the AISI 4130 steel was not influenced by the retained hydrogen, however, it was shown that the ZTA of the buttery like pulsed current mode and Inconel 625 is more susceptible to hydrogen fragility.